Pengaruh Terapi Relaksasi Autogenik terhadap Penurunan Intensitas Nyeri pada Pasien Syndrome Dispepsia di RSUD Prof. Dr. H. Aloe Saboe Kota Gorontalo - Yusuf, Mahdalia Salsabila; Rahma, Siti; Arsad, Sitti Fatimah Meylandri (Fakultas Ilmu Kesehatan, 2025)
Dyspepsia is one of the most common digestive complaints experienced by the community and can cause pain as well as discomfort in the upper abdomen, which may interfere with daily activities. To date, pain management efforts in dyspepsia patients generally involve pharmacological therapy such as the administration of antacids or acid-suppressing medications. However, the effects of these therapies are not always optimal, and some patients continue to experience recurrent pain symptoms. Therefore, non-pharmacological therapy is needed to help reduce pain symptoms independently, one of which is autogenic relaxation therapy that focuses on the patient’s ability to create a sense of relaxation in their own body. The purpose of this study was to determine the effect of autogenic relaxation therapy on reducing pain intensity in patients with dyspepsia syndrome at Prof. Dr. H. Aloei Saboe Regional General Hospital, Gorontalo City. This research used a quantitative method with a pre-experimental design and a one-group pretest–posttest approach. The study sample consisted of 15 respondents selected using accidental sampling techniques. Pain intensity was measured using the Numeric Rating Scale, and the data were analyzed using the Wilcoxon test. The results showed that autogenic relaxation therapy had an effect on reducing pain intensity in patients with dyspepsia syndrome in the Emergency Department of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. The Wilcoxon test obtained a significance value of p = 0.000 (< 0.05). Based on these findings, it can be concluded that autogenic relaxation therapy is effective in reducing pain intensity among patients with dyspepsia syndrome and may serve as an alternative non-pharmacological intervention in dyspepsia pain management.